Media Audio Visual Aids (AVA) Dalam Meningkatkan Pemahaman Peserta Didik Pada Pembelajaran Biologi - Khoirunisa Ainul Fatihah; Innes Prameswary; Oktantia Almira Putri M; Asri Dwinta Butar-butar; Ade Suryanda (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This research discusses the role of Audio Visual Aids (AVA) Media in improving students' understanding of biology learning. The method used in this research is a qualitative approach with the technique of combining several data in the form of literature studies based on literature analysis related to the use of AVA media. The results showed that there was a significant increase in understanding in students compared to learning that did not use audio visual aids (AVA) in biology learning, accompanied by positive responses from students to the use of AVA. The findings support the importance of AVA integration in Biology learning, encouraging interactive and innovative approaches. This research is expected to provide guidelines for educators in improving the quality of Biology learning at the secondary education level.